Design, Development and Performance Study of L3- Home Security System (Global Journals of Research in Engineering, 2012)
All over the world, security has been a major concern in every home. Here, a security system has been developed that uses sensors to detect any security violation and sends out the alert signal by high intensity Buzzer. The system mainly consists of LDR, Laser, Logic Gates, Microcontroller IC, LCD, Keypad and Relay Circuit. L3 stands for LDR, Laser and Logic Gates as these 3 components form the core idea of the system. This system is mainly implemented on the present doors with lock-key method. Thus providing Double Authentication i.e. the door can only be opened with the right password and right key. Another feature of the system being that, using different logic gates combination the system is designed in such a way that the buzzer won#x2019;t be switched off even though the intruder cuts the wires connecting the Buzzer and main control circuit. The system is designed and developed using simple locally available components and by considering every tiny factor it is made both reliable and affordable. Performance and cost analysis studies are also carried and also a glance into the future upgradations such as SMS service, PIR sensors and IR sensors that be introduced in the system.
Keywords: Microcontroller; Sensors; LCD; Logic Gates; Laser